Textual Coherence In the Rayiyat of lbn Abdoun al -Yabri (D: 527AH) - ياسين سرى طه (Journal of College of Education, 2023)
The research deals with textual coherence in the Rayiyat poem of the Andalusian poet "Ibn Abdoun" al-Yabri, who worked as a minister and clerk for the family of Banu al-Muzaffar from Banu al-Aftas, who ruled Ptolemy between (421-487 AH). The poem was written in lamentation of that kingdom, which reached its end by the Almoravid leader Yusuf ibn Tashfin, who had crossed the strait from Morocco and entered Andalusia. This poem is considered one of the oldest elegies in Andalusia, and attributed the loss of this country to fate. The research sought to reveal how the poem was coherent and its verses were linked to each other through the employment of multiple grammatical and lexical mechanisms, each mechanism has its function to suit the contexts. The researcher developed a plan to show the textual coherence in the poem, it consisted of four topics. The research concluded with a conclusion with the results, and then a list of references.